Green taxation and renewable energy technologies adoption: A global evidence - Tii Njivukuh Nchofoung; Hervé Kaffo Fotio; Clovis Wendji Miamo (African Governance and Development Institute (AGDI), 2023)
There is substantial literature on the determinants of renewable energy consumption. This growing interest is related to the fact that renewable energy is not only one of the main drivers of greenhouse gas mitigation but also its contribution to the achievement of other sustainable goals. Despite this strategic role, the adoption level of renewable energy remains quite low. In this article, we address one of the determinants so far ignored by the literature, namely the environmental tax. This study, therefore, examines the effect of environmental taxes on the adoption of renewable technologies for 49 global samples between the 1996-2017 periods. The results through the FE Driscoll and Kraay, the Newey-West, the system GMM, and the quantile regression methodologies show that environmental tax increase the consumption of renewable energy. However, taking into account disparities in the level of development, the results suggest that the environmental tax spurs renewable energy technologies adoption in developed countries while it decreases renewable energy technologies adoption in developing countries. As policy implications, policymakers within this sample should consider the optimization of environmental taxation as a policy toward environmental protection. This would cause energy consumers to opt for renewable energy sources of energy to escape these taxes.
Keywords: 330; Green taxation; renewable energy; panel data; SDG7; environmental protection